2020
DOI: 10.4314/ahs.v20i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Sexual knowledge and practice of adolescent learners in a rural South African school

Abstract: Background: Premature sexual activity has become a norm in South African society, often resulting in teenage pregnancy and sexually transmitted diseases (STD). Occurrence of premature sexual activity is related to insufficient education, gender inequal- ities, household poverty and place of residence. The Stepping Stones project uses a 10-session programme to educate learners about relationships, HIV-prevention and teenage pregnancy. The purpose was to measure and describe learners’ sexual knowl- edge and acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…The results of the 9th journal (Mostert et al, 2020) can be concluded that the level of sexual activity is low among adolescents. However, many adolescents engage in unsafe sexual activities due to inconsistent use of contraceptives, this happens because most adolescents are not sexually active, accompanied by a low level of adolescent knowledge related to sexuality.…”
Section: Resultsmentioning
confidence: 95%
“…The results of the 9th journal (Mostert et al, 2020) can be concluded that the level of sexual activity is low among adolescents. However, many adolescents engage in unsafe sexual activities due to inconsistent use of contraceptives, this happens because most adolescents are not sexually active, accompanied by a low level of adolescent knowledge related to sexuality.…”
Section: Resultsmentioning
confidence: 95%
“…Across SSA, adolescent SRH services are inequitably distributed by region, gender, education, urban-rural residence, economic status, and HIV status (6). In a national survey of South African adolescents, the mean age for rst-time sexual intercourse was 15.2 years (7). Only 40.3% reported contraception use (7), which was dependent on knowledge, relationship status, age difference, accessibility of contraception, and healthcare worker attitudes (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…In a national survey of South African adolescents, the mean age for rst-time sexual intercourse was 15.2 years (7). Only 40.3% reported contraception use (7), which was dependent on knowledge, relationship status, age difference, accessibility of contraception, and healthcare worker attitudes (8,9). Peer interactions have an established effect on youth sexual behaviors (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The next three articles are on sexual behaviour and practice. They include: 'use of sachet alcohol and sexual behaviour among adolescents in Nigeria 3 ; sexual knowledge and practice of adolescent learners in rural South Africa 4 ; and sexual behaviours and risk perception of STIs among polytechnic students' in Nigeria 5 . The next group of papers are on, yes you have guessed right, infectious diseases.…”
mentioning
confidence: 99%